Co-pyrolysis of palm empty fruit bunch and palm kernel shell with palm oil mill effluent (POME) sludge - Navin Raj Vijiaretnam (2023)
In Malaysia, the largest contributor to biomass is from the palm oil sector. Therefore, palm-based biomass has been extensively studied for bioenergy applications. Fast pyrolysis of biomass provides a liquid fuel called bio-oil, which has many potential uses. However, a low pH of bio-oil made a challenge to utilize as it is. Therefore, in this study, empty fruit bunch (EFB) and palm kernel shell (PKS) were subjected to co-pyrolysis with POME sludge individually. The reason behind this was that the bio-oil derived from EFB and PKS are acidic, whereas bio-oil from POME sludge is basic. Hence, it was hypothesised that through the co-pyrolysis, bio-oil with lower acidity might be obtained. Chemical characterization revealed that POME sludge contains alkali and alkaline earth metals (AAEMs), which may play a significant role in influencing the weight loss of EFB and PKS, also the bio-oil yield. The co-pyrolysis of EFB and PKS with POME sludge at different ratios were initially carried out via thermogravimetric analysis (TGA). Results showed that for the co-pyrolysis of PKS, a positive synergistic effect was observed when 50 wt.% of POME sludge was employed. Then, pyrolysis and co-pyrolysis experiments were carried out in a fixed bed reactor at 600°C. The bio-oil yield obtained from PKS was 44.5 ± 0.7 wt.%. In contradiction to TGA studies, the bio-oil yield for co-pyrolysis of PKS and POME sludge showed a negative synergistic effect.